Respons Tanaman Padi Pada Media Tanam Tanpa-Tanah Berbasis Irigasi Berselang - Tirto Wahyu Widodo; Damanhuri Damanhuri; Ilham Muhklisin; Sonia Budiarti; Dian Agustina (Jurnal Ilmu Pertanian Indonesia, 2024)
Rice cultivation without land as an urban farming method is carried out to produce food in a subsistence manner. This experiment aimed to examine the response of rice plants to non-soil planting media based on alternate wetting-drying irrigation. This work was conducted at the screen house in Sumberjeruk Village, Jember Regency (8°07'42.9" S and 113°47'09.3" E) from January to May 2022, using a factorial, fully randomized design of 2-factors with 3-replications. The planting medium without soil (husk:water) as the first factor consists of 4 compositions (v/v): 0:1, 1:4, 1:6, and 1:8 (total volume of 25-L media), while variety as the second factor consists of Inpari 46 and IR 64. The results showed that the combination treatment (husk: water) 1:6 and Inpari 46 had a significant effect on the number of productive tillers (25.17 stems) and grain weight per hill (34.07 g). The planting medium of non-soil husk: water 1:6 gave no significant value to husk: water 1:4 on the total number of grains (124.21 grains) and full grains (83.52 grains). The Inpari 46 varieties showed the highest value for the total number of grains (133.07 grains), the number of full grains (84.88 grains), and the weight of 1000-seeds (22.43 g). The application of husks and water as a planting medium with the right ratio is an ideal medium for landless rice cultivation since it can supply oxygen to the media. Keywords: growth, production, rice, subsistence farming, soilless